ADDITION OF WHITE SHRIMP (Penaeus merguiensis) HEAD EXTRACT TO INCREASE PROTEIN CONTENT IN SHRIMP STICKS - Rabiatul Adawyah (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2016)
The objective of this study was to obtain a proper ratio between the volume of water and the weight of shrimp heads in order to increase the protein content in shrimp sticks. The design used in the study was a completely randomized design (CRD) with treatment groups of 1:1, 1:2, and a control group without the addition of shrimp head extract. Water content, protein content, ash content and organoleptic test were the parameters measured. The results of the study show that the addition of white shrimp head extract in the treatment group with a 1: 1 ratio produced shrimp sticks with a protein content of 12.22%; in the treatment group with a 1: 2 ratio 13.44%; and in the control group without the addition of shrimp head extract only 5.54%. The addition of shrimp head extract also produced more preferred flavor compared to the one without the addition of the extract.